Variation of compaction pressure on hardness and wear of motorcycle disc brake pads - Alvandi; Khanif Setiyawan; Andi Nugroho; Binyamin (Journal of Energy, Mechanical, Material, and Manufacturing Engineering, 2022)
The reason for this study was to decide the impact of coconut shell powder molecule size on the hardness and wear pace of aluminum epoxy based composites. This study employs four particle size configurations in an experimental approach. Commercial powders with a 100 m molecular size make up the arrangement. The highest and lowest hardness values that were achieved, respectively, were 195 kg/mm2, 198 kg/mm2, and 203 kg. However, the wear rates of 0.85,0.67, and 0.63 are the highest and lowest. Since specimens with a pressure of 203 produce the highest average hardness, it can be deduced that the hardness number shown is proportional to the greater pressure/compression treatment. In contrast, the specific wear value added for the thirst test is influenced by the presence of increased traction as a result of the pressing and compacting treatment.